Pengaruh Kualitas Produk, Word of Mouth, Promosi dan Harga Terhadap Keputusan Pembelian Produk My Dimsum - Dilla Berliani; Junita Lubis; Abdul Halim (CV. Ulil Albab Corp, 2024)
This research aims to test, analyze and explain the influence of product quality, word of mouth, promotion and price on purchasing decisions for My Dimsum products. This type of research is categorized as descriptive analytical research using a quantitative approach. The sample for this research consisted of 98 respondents consisting of My Dimsum consumers who were taken using accidental sampling. Data collection uses a questionnaire. The data analysis method uses multiple linear analysis with the SPSS (Statistical Product and Service Solution) application tool. Instrument testing uses validity tests and reliability tests. The research results show that product quality has a significant influence on purchasing decisions for My Dimsum products. Word of mouth has a significant influence on purchasing decisions for My Dimsum products. Promotion does not have a significant effect on the decision to purchase My Dimsum products and price has a significant effect on the decision to purchase My Dimsum products.